Intraguild predation between an exotic and a native coccinellid in Argentina: the role of prey density - Mirande, Luciana (2015)
Harmonia axyridis Pallas is a generalist predator native to Asia. It has been released both for classical and neoclassical biological control programs worldwide. Its presence has led to new ecological associations and it has been associated with the decline of indigenous natural enemies, notably ladybirds. These declines have been attributed to competition for resources and intraguild predation (IGP). H. axyridis was introduced in Argentina in 1986 to control the aphid Myzus persicae, although native coccinellid species are widespread in this area. Eriopis connexa Germar is the most abundant native coccinellid in Argentina. No study has assessed the possible ecological effects of the introduction of H. axyridis on naturally occurring aphid predators in Argentinian agro-ecosystems. This study evaluated IGP between H. axyridis and E. connexa at two different aphid densities under laboratory conditions. IGP occurred in 100 % of the cases when larvae of both species were reared together at low prey density and in 67 % of the cases at high prey density; at both prey levels, H. axyridis usually acted as the IG predator. The more rapid development to second and third larval instars, larger body size, and more voracious behavior of H. axyridis compared to the native coccinellid could explain the IGP direction. This study showed the negative effect of H. axyridis on the native E. connexa under laboratory conditions, corroborated interactions between the species observed in field crops, and highlighted the impacts of this exotic predator on naturally occurring predator species.